A SURVEY OF PHARMACY STAFF KNOWLEDGE RELATED TO ANTIBIOTICS IN SIDOARJO, INDONESIA - Ilil Maidatuz Zulfa; Fitria Dewi Yunitasari (Universitas Muhammadiyah Magelang, 2020)
Antibiotics resistance still remains the problem in treating infection disease both in developing and developed country. One of the factor contribute to the increase of antibiotics resistance is irrational antibiotics use without prescriptions. There is still lack of information about factors related to the antibiotics dispense by pharmacy staff. This study was aimed to observe pharmacy staff knowledge about the pharmacology and the regulation of antibiotics. A cross sectional online survey using questionnaire was conducted to pharmacy staff who work for service in Sidoarjo from February to April 2020. The knowledge of antibiotics was classified into lack, enough, and good knowledge. A total of 233 respondents from 56 pharmacy recruited in this study. Of them, 17,17% were pharmacist; 10,73% were pharmacy technician; 52,36% were pharmacy assistant and 19,74% non pharmacy worker. Overall the majority of respondents had a good knowledge about antibiotics (48,93%). However, most of them did not know that only pharmacist who had responsible to dispense antibiotics based on prescriptions (58,37%), fail to describe antibiotics indications (46,35%) and had poor knowledge about the minimum length of antibiotics course (58,37%). Educating and upskilling pharmacy personel about antibiotics will minimize the irrational use of antibiotics which lead to the increase of antibiotics resistance caused by the lack information received by patients.